URGENSI ETIKA PROFESI PENGEMBANGAN MASYARAKAT ISLAM - Icol Dianto (Fakultas Dakwah dan Komunikasi, 2018)
Ethics becomes a guiding tool in running a profession. Profession is not only defined as work done with skill or expertise, because in fact the profession includes mastery of theoretical knowledge, theoretical (practical) and experiential implementation. Similarly, the work of the community facilitator profession, which requires an ethical standard to be used as a guide in carrying out its work.Using ethical comparative analysis according to Western and Islamic philosophy, which then attempts to formulate the urgency of the ethical profession of Islamic community facilitator, which includes (a) Guidelines for community facilitator to carry out their duties and responsibilities, (b) the system of norms for professional development and personality, c) benchmark in evaluating the professionalism of community facilitator work.